Boron-mediated modular assembly of tetrasubstituted alkenes - Liang Wei; Mihai V. Popescu; Adam Noble; Robert S. Paton; Varinder K. Aggarwal (Nature, 2025)
Abstract Alkenes are a central part of organic chemistry 1–3 . However, although most alkenes are easy to prepare, the controlled synthesis of tetrasubstituted alkenes, those with four groups around the central C=C bond, remains challenging 1–5 . Here we report the boron-mediated assembly of tetrasubstituted alkenes with complete control of the double-bond geometry. The migrating group and electrophile add syn across the alkyne. Mild oxidation leads to intermediate borinic esters 6 , which can be isolated and purified or reacted directly in a range of transformations, including cross-couplings and homologation reactions. In particular, subjecting the intermediate borinic esters to Zweifel 7,8 olefination conditions can give either retention or inversion of the double-bond geometry, depending on whether base is present or not. Different positional and stereoisomers of the tetrasubstituted alkenes can be easily accessed, highlighting the breadth and versatility of the method. This was showcased through its successful application to the rapid synthesis of drug molecules and natural products with high yield and stereocontrol. Not only does this method provide efficient access to the long-standing challenge of the stereocontrolled synthesis of tetrasubstituted alkenes but it also introduces new concepts related to the intervention of non-classical borenium ions in the Zweifel olefination.